Synthesis, structure and substitution mechanism of manganese Mn doped barium hexaferrite BaFe12-xMnxO19 - S.A. Gudkova; V.E. Zhivulin; G.M. Zirnik; L.A. Pesin; R.G. Chumakov; A.S. Chernukha; I.A. Solizoda; K.P. Gafarova; D.A. Vinnik (Results in Chemistry)
Polycrystalline BaFe12-xMnxO19 samples (x = 0–2, step 0.5) were synthesized by the ceramic technique. The dopant content in the ceramics was controlled by its charge content. The results of energy dispersive X-ray analysis, X-ray diffraction, X-ray photoelectron spectroscopy (XPS) were discussed. The elemental analysis results confirm that the obtained composition of ceramics is close to that specified in the initial charge. X-ray diffraction analysis based on La Bail refinement demonstrated that all BaFe12-xMnxO19 samples are single phase ones with the P63/mmc magnetoplumbite structure. The effect of manganese substitution on the barium hexaferrite based solid state solutions crystal structure was studied. Fine structure different iron and manganese ions oxidation states were observed as the result of XPS investigation. For the highest substitution level sample brutto formula was specified as BaFe2+3.3Fe3+6.6Mn2+0.5Mn3+1.4Mn4+0.2O19. The two substitution mechanisms for case of divalent ions substitution in barium hexaferrite were formulated. The first one is when the divalent ion of iron or manganese takes the barium position, and the second one is when the dopant takes the Fe3+ position of the initial crystalline matrix and creates a broken bond with oxygen.